2022
DOI: 10.1186/s43055-022-00941-7
|View full text |Cite
|
Sign up to set email alerts
|

Diagnostic performance of pre-management computed tomography findings as a predictor of conservative treatment success in patients with emphysematous pyelonephritis

Abstract: Background Emphysematous pyelonephritis (EPN) is one of the most serious urologic emergency which should be diagnosed and treated adequately to prevent impending septic shock and death. Computed tomography (CT) is the gold standard radiologic modality for diagnosis, grading and predicting the outcome. We aimed in this study to define the initial CT radiological findings correlated with EPN conservative management success. Results This study involv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 15 publications
0
4
0
Order By: Relevance
“…CT findings play a pivotal role in guiding the therapeutic approach for EPN [ 11 ]. When functional kidney tissue is present, the initial treatment typically involves the administration of antibiotics, fluid resuscitation to restore hydration, and management of blood sugar levels, particularly in diabetic patients.…”
Section: Discussionmentioning
confidence: 99%
“…CT findings play a pivotal role in guiding the therapeutic approach for EPN [ 11 ]. When functional kidney tissue is present, the initial treatment typically involves the administration of antibiotics, fluid resuscitation to restore hydration, and management of blood sugar levels, particularly in diabetic patients.…”
Section: Discussionmentioning
confidence: 99%
“…Perinephric and intraparenchymal fluid accumulation are seen on MRI. [19,20] On the basis of radiological findings on CT scan jj huang et al classified EPN into 4 classes, Huang and Tseng staging protocols: [7]  Class 1: Gas in the collecting system  Class 2: Gas restricted to renal parenchyma  Class 3A: Perinephric gas or abscess extension  Class 3B: Gas extension beyond the Gerota's fascia  Class 4: Bilateral or single-kidney EPN…”
Section: Discussionmentioning
confidence: 99%
“…A study done by MA Badaway et al over 16 years from 2000 to 2016 in 54 patients found that the presence of air locule volume >54 cc and hydronephrosis were associated with 12 and 5.5 folds of risk of failure of conservative treatment (7).…”
Section: Distinctive Diagnosismentioning
confidence: 99%
“…Estimated GFR (eGFR) in mL/min/1.73 m 2 was calculated using EPI-CKD formula [9]. Radiological evaluation by noncontrast computed tomography was reviewed for the presence of distal obstruction, grades of EPN [lower grades (I, II) and high grades (III, IV)] [3], and air locule volume in mm 3 [8,10]. Available follow-up renography data were also reviewed.…”
Section: Methodsmentioning
confidence: 99%